Survey of Health Care Providers' Practices and Opinions Regarding Bacterial Sexually Transmitted Infection Testing Among Gay, Bisexual, and Other Men Who Have Sex With Men. Issue 2 (February 2021) - Rana, Jayoti; Guiang, Charlie B.; Lisk, Ryan; Shahin, Rita; Brunetta, Jason; Mitterni, Leo; Grewal, Ramandip; Tan, Darrell H.S.; Gilbert, Mark; Yeung, Anna; Kwag, Michael; Logie, Carmen H.; et al.
Abstract : Background: Rates of bacterial sexually transmitted infections (STIs) continue to rise among gay, bisexual, and other men who have sex with men (GBMSM) globally. Testing and treatment can prevent morbidity and transmission. However, testing rates remain suboptimal. Methods: In 2018, we conducted an online cross-sectional survey to explore STI testing ordering practices, 14 potential barriers for testing and 11 possible ways to improve testing from the perspective of health care providers in Toronto, Ontario. An estimated 172 providers were invited from primary care and sexual health clinic settings. Providers were eligible to complete the survey if they provided care for ≥1 GBMSM per week and were involved in the decision-making process in providing STI tests. We used descriptive statistics to summarize survey responses. Results: Ninety-five providers (55% response rate) participated, of whom 68% worked in primary care and 32% in sexual health settings. Most (66%) saw ⩽10 GBMSM clients per week. In primary care (65%) and sexual health (40%) clinic settings, insufficient consultation time was the most common barrier to STI testing. In primary care, other common barriers included difficulty introducing testing during unrelated consultations (53%), forgetting (47%), and patients being sexually inactive (31%) or declining testing (27%). The following were most likely to improve testing: express/fast-track testing services (89%), provider alerts when patients are due for testing (87%), patient-collected specimens (84%), nurse-led STI testing (79%), and standing orders (79%). Conclusions: Promising interventions to improve bacterial STI testing included initiatives that simplify and expedite testing and expand testing delivery to other health care professionals. Abstract : Express testing, patient-collected specimens, standing orders for tests, and delegation to other health care professionals were favored methods to improve bacterial sexually transmitted infection testing delivery among surveyed health care providers.